Pachyphytum brevifolium Rose (Crassulaceae) a un siglo de su descubrimiento y Pachyphytum garciae una especie nueva del centro de México - Perez-Calix, Emmanuel; Glass, Charles (Instituto de Ecología, A.C., 1999)
Two localities for Pachyphytum brevifolium from the state of Guanajuato are reported. This species had not been found since its discovery by Alfred A. D. Dugès in 1898. A description of the collected plants is presented and their relationship with other species of the genus is discussed. Pachyphytum garciae is described as a new taxon. It partially resembles Pachyphytum fittkaui Moran in its elliptic, elliptic-oblanceolate, obovate to obovate-spathulate leaves, but it differs in its smaller, non-imbricate bracts, as well as in the length and thickness of its pedicels, which separate it not only from P. fittkaui but also from the section Ixiocaulon. P. garciae Moran is also closely related to P. caesium, but differs in the color of the lobes of the corolla, as well as in the form and dimension of the leaves.